Language Development of Children aged 6-8 years in the Rato Village Community, Manggengula Hamlet, Bolo District, Bima Regency - Dimas, Dimas; Haris, A.; Ikra, Ikra; Arwan, Arwan (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aimed to determine and observe children's language development in Rato Village, Bolo District, Bima Regency. This research is qualitative research using qualitative descriptive methods. Data is analyzed based on theories and phenomena from the aspects studied. The data used in this research are sentences spoken by children aged 6-8 years in Rato village. The data source used in this research comes from daily conversations of 6 children aged 6-8 in Manggengula hamlet, Rato village. Data comes from journals and books as theories relevant to this research. The data collection techniques used in this research are observation and documentation. The data analysis technique in this research uses descriptive analysis techniques. The researchers' results found that the language development of children aged 6-8 years in the Rato Village Community, Manggengula Hamlet, Bolo District, Bima Regency is not the same. Language is learned through habituation from the environment and is the result of the imitation of adults. Language is something that is acquired naturally. Some factors influence the acquisition of a second language in children, namely: the age factor, because when you are still a child it will be easier to acquire a second language; the first language factor (mother), because the first language greatly influences the grammar of other languages; environmental factors, the environment is a very important factor for children's language acquisition because children aged up to 6 years will acquire and speak the language they often hear from the environment, especially family, friends and the community